COMPARABILITY OF THE RESULTS OF SEROLOGICAL MONITORING FOR LARVAE ECHINOCOCCUS GRANULOSUS AND TAENIA HYDATIGENA IN INFECTED SHEEP - V. K. Berezhko; A. A. Thakahova (Российский паразитологический журнал, 2016)
The results of serological monitoring of larvae Echinococcus granulosus (Egl) and Taenia hydatigena (Thl) of sheep in farms of different zones of the Kabardino-Balkariya Republic carried out using the enzyme-linked immunosorbent assay (ELISA) and the comparability of the immunoassay data with the rate of animal infestation are presented. Materials and methods 225 blood serum samples collected from sheep were examined. As antigens for ELISA test served the excretory secretory products from Echinococcus granulosus (Egl) and Taenia hydatigena (Thl) protoscoleces, as conjugate – affinity purified, specific to sheep immunoglobulin, peroxidase labeled rabbit antigens. Results and discussion It was found that the sensitivity of immunoassay for antigen from protoscoleces Egl was 75,6–77,8 %, and from protoscoleces Thl – 71,1–75,6 %. The specificity of ELISA estimated using the blood serum from clinically healthy sheep was: for antigen from protoscoleces Egl 73,3 %, and from protoscoleces Thl – 71,1 %. The differences between the number of sheep giving a positive reaction to ELISA tests and the rate of infestation with cestodes based on the results of postmortem examination were determined. The data of the enzyme-linked immunosorbent assay (ELISA) of sheep blood sera matched with the data of the animal infestation rate with Echinococcus granulosus (Egl) in 88,2–91,4 %, and Taenia hydatigena, larvae (Thl) – in 81,3–93,5 %, on the average 90,0 and 86,5 % respectively. Thus, we can make a conclusion that the enzyme-linked immunosorbent assay (ELISA) for the presence of parasite antigens in protoscoleces can be used for the seroepizootological monitoring for cystic echinococcosis and cysticercosis (Thl).